2023
DOI: 10.2147/cia.s395228
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Vitamin D Deficiency is Associated with Increased One-Year Mortality in Chinese Geriatric Hip Fracture Patients – A Propensity Score Matching Study

Abstract: Background Vitamin D deficiency is a common comorbidity in geriatric hip fracture patients. However, there is still an ongoing debate regarding the influence of preoperative Vitamin D status on postoperative mortality in hip fracture patients. Methods Elderly patients (≥60 years) who underwent surgical interventions for unilateral hip fracture from 2015 to 2020 in our center were included. We retrospectively retrieved the demographic data from the electronic medical dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…No relevant unpublished studies have been published to date. Ultimately, a total of nine studies were included in the meta‐analysis 7,15–22 …”
Section: Resultsmentioning
confidence: 99%
“…No relevant unpublished studies have been published to date. Ultimately, a total of nine studies were included in the meta‐analysis 7,15–22 …”
Section: Resultsmentioning
confidence: 99%
“…More specifically, preoperative serum 25(OH)D > 12 ng/mL were associated with 30- and 60-day increased mobility [ 77 ]. Subsequent retrospective analyses confirmed the association between pre-surgical vitamin D deficiency and 6- or 12-month worse physical outcomes, re-admission for medical issues, and re-fracture in elderly subjects [ 78 , 79 , 80 ]. More recently, a meta-analysis of these and other studies in a total of 1972 hip fractured patients aged 78–84 demonstrated that vitamin D deficiency was associated with poorer quality of life and functional ability after fracture, while it did not influence the walking ability and length of stay in the hospital [ 74 ].…”
Section: Vitamin D Status and Hip Fracturesmentioning
confidence: 89%
“…While various factors may contribute to patients’ survival after surgical procedures, it is worth mentioning that 12 of 13 patients in the present study had a vitamin D level below the normal range (<30 ng/mL). A large body of evidence has demonstrated that higher postoperative mortality rates among hip fracture patients are linked to lower levels of vitamin D at 30 days [ 33 ], 1 year [ 34 , 35 , 36 , 37 ], and 2 years [ 36 ] of follow-up. The pooled data of a recent meta-analysis on femur fracture patients revealed that vitamin D insufficiency and severe deficiency are associated with increased mortality in patients with hip fractures.…”
Section: Discussionmentioning
confidence: 99%